Organ donation in the paediatric intensive care unit: Time for change? - Kristy Xinghan Fu; Sze Lyn Jasmin Jeanette Tan; Ne-Hooi Will Loh (Annals, Academy of Medicine, Singapore)
Organ transplantation remains the definitive treatment option for improving the lives of patients with end-stage organ failure. To our knowledge, the first solid organ transplantation performed in Singapore in July 1970 involved a kidney from a deceased donor.1 Since then, rapid advancements in both transplant surgery and immunosuppressive medical therapy have enabled solid organ transplantation to better meet the increasing demands of a growing Singapore population with end-organ diseases. Yet, the supply of donor organs lags behind the demand.2